Analisis Variasi Nilai Time Inversion (TI) Terhadap Infromasi Citra MRI Knee Joint Potongan Sagital Sekuen PDW SPAIR - Widiatmoko, Mahfud Edy; Sabina, Asy Syifa; Supriyaningsih, Eny; Rizqi, Muhammad; Hidayat, Eka Putra Syarif (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: Magnetic Resonance Imaging (MRI) is a non-invasive imaging modality essential for evaluating complex anatomical structures such as the knee joint. MRI allows multiplanar imaging with high soft tissue contrast resolution. In knee imaging, the sagittal plane is particularly effective in assessing pathologies and visualizing structures like cartilage, menisci, bones, and ligaments (ACL and PCL). Proton Density Weighted (PDW) sequences combined with Spectral Adiabatic Inversion Recovery (SPAIR) fat suppression are commonly used to enhance soft tissue visualization. The image quality in SPAIR sequences is significantly influenced by the Time Inversion (TI) parameter. This study aimed to analyze the impact of varying TI values on the image quality of sagittal PDW SPAIR MRI of the knee joint, focusing on anatomical detail and contrast resolution.Methods: This research used a quantitative analytical method with an experimental approach. The study was conducted at the Radiology Department of Pertamina Central Hospital from March to April 2025. Ten knee MRI examinations were selected as samples. Image quality was assessed by three radiologists using a structured scoring questionnaire. The data were analyzed using non-parametric statistical tests, including Friedman and Wilcoxon Signed-Rank tests.Results: The Friedman test revealed statistically significant differences in anatomical detail (Ï‡Â²(2) = 15.000, p = 0.001) and contrast resolution (Ï‡Â²(2) = 17.882, p = 0.000) across the three TI values (100 ms, 160 ms, and 200 ms). Post-hoc Wilcoxon analysis showed that both TI 160 ms and 200 ms provided significantly higher image quality than 100 ms (p < 0.017) in both parameters. However, no significant differences were found between TI 160 ms and 200 ms (p = 0.506 for anatomical detail, p = 0.273 for contrast resolution). Among the values tested, TI 160 ms demonstrated consistent and optimal scores for both image clarity and contrast.Conclusions: A TI value of 160 ms in the PDW SPAIR sequence is recommended as the optimal parameter for producing superior sagittal MRI images of the knee joint, particularly in terms of anatomical clarity and contrast resolution.